Peer problems are associated with elevated serum leptin levels in children. Issue 2 (January 2014) - Kohlboeck, G.; Romanos, M.; Tiesler, C.; Koletzko, S.; Kratzsch, J.; Thiery, J.; Bauer, C.-P.; von Berg, A.; Berdel, D.; Hoffmann, B.; Schaaf, B.; Lehmann, I.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Leptin is thought to act as an important mediator in stress reactions. To date, no study has examined the association between psychological stress and leptin levels in children. This study aimed to assess the association between emotional symptoms and peer problems and serum leptin levels in children aged 10 years of the two population-based GINI-plus and LISA-plus birth cohorts. Method Cross-sectional data from 2827 children aged 10 years were assessed with regard to leptin concentrations in serum and behavioral problems using the parent-reported Strengths and Difficulties Questionnaire (SDQ). Linear regression modeling was applied to determine the likelihood of elevated leptin levels in children with emotional symptoms and peer problems, controlling for socio-economic status (SES), body mass index (BMI), fasting serum leptin levels, pubertal development and sex hormones. Results We found that increases in emotional symptoms (exp βadj = 1.03, s.e. = 0.02, p < 0.04) and peer problems (exp βadj = 1.05, s.e. = 0.01, p = 0.0001) were significantly associated with higher serum leptin levels controlled for BMI and sociodemographic factors. Similar results were found when the fasting serum leptin sample was examined (exp βadj = 1.08, s.e. = 0.04, p = 0.0294). Gender-stratified analyses showed a significant relationship between serum leptin and peer problems in girls (exp βadj = 1.05, s.e. = 0.02, p = 0.03), and a borderline significant association in boys (exp βadj = 1.04, s.e. = 0.02, p = 0.05). Conclusions Children with peer problems have higher stress and eat more, acquire a higher body fat mass and thus, through increased leptin resistance, exhibit higher leptin levels.